CEO Characteristics and Their Impact on Financial Distress: Evidence from Indonesia’s State-Owned Non-Financial Enterprises - Adien Husnun Nabila; Fitra Dharma; Liza Alvia (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2025)
Company performance can be influenced by internal managerial factors, particularly the characteristics of the Chief Executive Officer (CEO), including age, gender, educational background, experience, and CEO duality. Guided by the Upper Echelon Theory, this study aims to examine the effect of CEO characteristics on financial distress in non-financial state-owned enterprises (SOEs) in Indonesia. The research population includes SOEs listed on the Indonesia Stock Exchange from 2020 to 2024. Using purposive sampling, 95 firm-year observations were selected and analyzed using multiple linear regression. The results reveal that CEO gender, education, and duality have a significant positive effect on financial distress, while CEO age and experience do not have a statistically significant impact. These findings suggest that leadership attributes, especially CEO structure and educational attainment, are important determinants in mitigating or exacerbating a firm's financial vulnerability. The study provides insights for policymakers and boards of commissioners in improving CEO appointment criteria to enhance the financial sustainability of SOEs.